Effects of a 12 week community-based high-level mobility programme on sustained participation in physical activity by adolescents with cerebral palsy: a single subject research design study - Kilgour, Gaela; Stott, Ngaire Susan; Steele, Michael; Adair, Brooke; Hogan, Amy; Imms, Christine (Disability and rehabilitation, 2024)
To assess if a high-level mobility programme (HLMP) can promote sustained participation in physical activity by adolescents with cerebral palsy. Eight adolescents with cerebral palsy, Gross Motor Function Classification System levels I-II, 11-16 years, participated in 24 community-based group HLMP sessions across 12 weeks. Participants set attendance, involvement, and physical performance goals, completed activity diaries over 58 weeks and undertook physical capacity tests. Measures of activity frequency and diversity (attendance) and involvement level were collected weekly across baseline (4-6 weeks), intervention (12 weeks), and nine months follow-up (including Covid lockdown). Median attendance was 23 of 24 HLMP sessions. Attendance goal/s attainment was highest during COVID lockdown. Involvement goals were consistently attained throughout all phases. Physical performance goal/s attainment was highest during intervention phase but reduced during nine months follow-up. Frequency of participation in physical activities varied greatly across study phases (range 0-33 episodes/week) with stable variety of activities and generally high 'involvement.' During the intervention, seven participants improved physical capacity and six maintained, or increased, the gains six months later. Most participants improved physical capacity post-intervention but only some had sustained attendance and involvement in physical activity, highlighting the complexity of physical activity participation.